Thromboelastography Profile of Covid-19 Patients Before and After Convalescent Plasma Therapy Administration - Fatonah, Siti; Hartanti, Khoirunisah Dwi; Purnamasari, Putri; Ningtyas, Denina Setya; Ramadhani, Saskia; Xaveria, Xaveria (Fakultas Kedokteran Universitas Brawijaya, 2024)
In Covid-19 patients, coagulopathy disorder is commonly characterized as hypercoagulable, although hemorrhagic complications can arise. However, thromboelastography (TEG) is an examination tool with the ability to assess the complete hemostasis process, including primary, secondary, and fibrinolysis stages, closely resembling the in vivo coagulation process. Therefore, this study provides a descriptive analysis of the hemostatic state of Covid-19 patients before and after administration of convalescent plasma therapy using TEG. In this study, the blood sample was collected from 21 Covid-19 patients at RSSA Malang from June to November 2020, followed by a TEG examination, which was performed on the first day of admission and after convalescent plasma therapy administration. The results were analyzed descriptively. Before convalescent plasma therapy, coagulation index (CI) analysis of TEG results in 21 patients showed that 62% exhibited normocoagulability, 23.8% were hypercoagulable, and 14.2% used hypercoagulability. While TEG results after convalescent plasma therapy showed that 71.4% were normocoagulable, 4.7% hypocoagulable, and 23.9% hypercoagulable. Based on TEG parameters, R, K, and MA, before administration of convalescent plasma therapy showed decreased platelet function by 38%, primary fibrinolysis by 5%, secondary fibrinolysis by 10%, platelet hypercoagulability 5%, and 43% was normal. Coagulopathy profile after convalescent plasma therapy showed decreased platelet function by 24%, secondary fibrinolysis by 10%, platelet hypercoagulability by 10%, enzymatic hypercoagulability by 5%, enzymatic and platelet hypercoagulability by 5%, and 48% was normal. TEG in Covid-19 patients showed a hypercoagulable state before and after administration of convalescent plasma therapy